The betrayal of Maggie Blair - Laird, Elizabeth (Boston : Houghton Mifflin, 2011)
In seventeenth-century Scotland, sixteen-year-old Maggie Blair is sentenced to be hanged as a witch but escapes to the home of her uncle, placing him and his family in great danger as she risks her life to save them all from the king's men.
Publisher's Weekly
School Library Journal starred
Wilson's Junior High School
Booklist, April 2011
Bulletin (Center for Children's books), March 2011
Horn Book, September 2011
Keywords: Betrayal -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; Uncles -- Juvenile fiction; Witchcraft -- Juvenile fiction; Betrayal -- Fiction; Fugitives from justice -- Fiction; Historical fiction; Uncles -- Fiction; Witchcraft -- Fiction; Betrayal -- Fiction; Criminals -- Fiction; Historical fiction; Uncles -- Fiction; Witchcraft -- Fiction; Scotland -- History -- 17th century -- Juvenile fiction; Scotland -- History -- 17th century -- Fiction; Scotland -- History -- Fiction; Historical fiction